FUNGSI KOMISI PENANGGULANGAN AIDS (KPA) DALAM PENANGGULANGAN HIV/AIDS DI KOTA PEKANBARU - Muhammad Tesar; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The development and population growth in Pekanbaru City over time also increases every year and causes various problems in the health sector, one of which is the increase in cases of HIV/AIDS in Pekanbaru City that can threaten public health. With these several causes, the AIDS prevention commission (KPA) must be extra in prevention and prevention efforts. So that the goals of the response to HIV/AIDS in the city of Pekanbaru can be overcome and slowly decline. Based on Pekanbaru Mayor Regulation Number 32 Year 2013 Concerning HIV and AIDS Prevention and Management in Pekanbaru City. The purpose of this study was to determine and analyze the function of the AIDS prevention commission (KPA) and to determine the inhibiting factors of the function of the AIDS prevention commission (KPA) in the prevention of HIV/AIDS in Pekanbaru City. The concept of theory used is the theory of organizational functions from Wursanto, (2002: 268), namely: Activities of planning, Organizing, Motivating, Controling, and Decision making. This study uses a qualitative method with a case study approach, with data collection techniques including: observation, interviews and documentation. The results of this study found that the function of the AIDS prevention commission (KPA) in the response to HIV/AIDS in Pekanbaru City was not yet optimal. The inhibiting factors in the response are communication, facilities and infrastructure, human resources, and budget. As well as community participation and stigma that still thinks to know ODHA, so that HIV/AIDS prevention is not yet realized. Keywords: Organization, Organization Function, and HIV/AIDS Control